Tensions and contradictions in Australian social policy reform: compulsory Income Management and the National Disability Insurance Scheme. Issue 4 (December 2016) - Marston, Greg; Cowling, Sally; Bielefeld, Shelley
Abstract : This paper explores contemporary contradictions and tensions in Australian social policy principles and governmental practices that are being used to drive behavioural change, such as compulsory income management. By means of compulsory income management the Australian Government determines how certain categories of income support recipients can spend their payments through the practice of quarantining a proportion of that payment. In this process some groups in the community, particularly young unemployed people and Indigenous Australians, are being portrayed as requiring a paternalistic push in order to make responsible choices. The poverty experienced by some groups of income support recipients appears to be seen as a consequence of poor spending patterns rather than economic and social inequalities. By contrast, Australia's National Disability Insurance Scheme (NDIS) has been constructed as a person centred system of support that recognises the importance of both human agency and structural investment to expand personal choices and control. Here we look at the rationale guiding these developments to explore the tensions and contradictions in social policy more broadly, identifying what would be required if governments sought to promote greater autonomy, dignity and respect for people receiving income support payments in Australia.